Modeling for Design Optimization of Piston Crown Geometry Through Structural Strength and Lubrication Performance Correlation Analysis - Mishra, Prakash Chandra; Kumar, Santosh (Frontiers in Mechanical Engineering, 2019)
Piston subsystem is subjected to very complex but dynamic forces. Such forces include combustion gas force, inertial dynamics forces, lubricating action/damping forces, contact friction forces to name a few. Further, piston ring mounted in piston in addition to these forces experiences out ward springing action inside engine mounting due to inherent elasticity. To evaluate the strength of reciprocating piston, the simultaneous effect of all these forces should be considered, while simulating it through FEM. With effect of all these forces, the currently considered piston of Grey Cast Iron, Al-alloy and Metal-Metric-Composite (Si-C) are given four different crown shapes for optimization of material and crown geometry. The rings mounted are considered to be coated with Nickasil. The combined numerical simulation for contact and FEM simulation of structural strength and their correlation suggest many important outcomes.